Positive childhood experiences reduce suicide risk in Japanese youth with ASD and ADHD traits: a population-based study - Masaki Adachi; Masaki Adachi; Masaki Adachi; Michio Takahashi; Michio Takahashi; Michio Takahashi; Hiroyuki Mori; Hiroyuki Mori (Frontiers in Psychiatry)
ObjectiveThis study investigated the combined influence of autism spectrum disorder (ASD) traits, attention-deficit/hyperactivity disorder (ADHD) traits, and positive childhood experiences (PCEs) on suicide-related behaviors in a large, representative sample of Japanese adolescents and young adults. Additionally, it explored the role of PCEs in mitigating the risks associated with neurodivergent traits.MethodsData were collected from 5,000 individuals aged 16–25 years using validated scales to measure ASD traits, ADHD traits, PCEs, and suicide-related behaviors, including suicidal ideation and attempts. Hierarchical regression analysis was conducted in multiple steps to assess the influence of these variables. Interaction effects between PCEs and neurodivergent traits were examined to determine potential moderating effects.ResultsASD traits and ADHD traits were positively associated with suicidal ideation, with the highest risks observed among individuals with elevated levels of both traits. The inclusion of PCEs demonstrated a significant negative association with suicidal ideation, indicating that individuals with more PCEs reported lower levels of suicidal ideation. PCEs also reduced the strength of the associations of ASD traits (from β = 0.180 to β = 0.092) and ADHD traits (from β = 0.216 to β = 0.185) with suicidal ideation. Interaction analyses showed that the protective effect of PCEs on suicidal ideation was particularly pronounced among individuals with high levels of ADHD traits. Simple slope analyses demonstrated that higher levels of PCEs were significantly associated with reduced suicidal ideation for those with both low (β = −0.339, z = −18.61, p < 0.001) and high levels of ADHD traits (β = −0.475, z = −21.84, p < 0.001), with a stronger effect for the latter group.ConclusionThese findings highlight the cumulative and potentially compounding effects of ASD and ADHD traits on suicide risk while underscoring the critical protective role of PCEs. PCEs can mitigate emotional dysregulation and impulsivity, particularly in individuals with high levels of ADHD traits, thus reducing suicide-related behaviors. This study underscores the importance of fostering PCEs as part of targeted interventions to promote resilience and mental health in vulnerable populations.